Demographic and clinical characteristics of patients with delirium: analysis of a nationwide Japanese medical database. Issue 9 (14th September 2022) - Ueda, Naoya; Igarashi, Masakazu; Okuyama, Kotoba; Sano, Hideki; Takahashi, Kanae; P Qureshi, Zaina; Tokita, Shigeru; Ogawa, Asao; Okumura, Yasuyuki; Okuda, Shoki
Abstract : Objectives: Delirium commonly occurs during hospitalisation and is associated with increased mortality, especially in elderly patients. This study aimed to determine the demographic and clinical characteristics of patients with delirium in the Japanese real-world clinical setting using a nationwide database comprising claims and discharge abstract data. Design: This was an observational, cross-sectional, retrospective study in hospitalised patients with an incident delirium identified by a diagnosis based on International Classification of Diseases, 10th Revision codes or initiating antipsychotics recommended for delirium treatment in Japan during their hospitalisation. Setting: Patients from the Medical Data Vision database including more than 400 acute care hospitals in Japan were evaluated from admission to discharge. Participants: Of the 32 910 227 patients who were included in the database between April 2012 and September 2020, a total of 145 219 patients met the criteria for delirium. Primary and secondary outcome measures: Demographic and baseline characteristics, comorbidities, clinical profiles and pharmacological treatments were evaluated in patients with delirium. Results: The mean (SD) patient age was 76.5 (13.8) years. More than half of the patients (n=82 159; 56.6%) were male. The most frequent comorbidities were circulatory system diseases, observed in 81 954 (56.4%) patients. Potentially inappropriate medications (PIMs) with risk of delirium including benzodiazepines and opioids were prescribed to 76 798 (52.9%) patients. Approximately three-fourths of these patients (56 949; 74.2%) were prescribed ≥4 PIMs. The most prescribed treatment for delirium was injectable haloperidol (n=82 490; 56.8%). Mean (SD) length of hospitalisation was 16.0 (12.1) days. Conclusions: The study results provide comprehensive details of the clinical characteristics of patients with delirium and treatment patterns with antipsychotics in the Japanese acute care setting. In this patient population, the prescription rate of injectable haloperidol and PIMs was high, suggesting the need for improved understanding among healthcare providers about the appropriate management of delirium, which may benefit patients.